Biochemical Scoring System For Diagnosing Nonalcoholic steatohepatitis - Alam, Sheikh Mohammad Noor E; Alam, Shahinul; Das, Dulal Chandra; Mahtab, Mamun Al (Bangladesh Journal of Medicine, 2019)
Background: Nonalcoholic fatty liver disease (NAFLD) encompasses a spectrum of conditions ranging from simple steatosis to steatohepatitis, advanced fibrosis, and end stage liver disease. Despite the high prevalence and severity of hepatic illness, NAFLD remains underdiagnosed, because of few symptoms, lack of accurate laboratory markers. Objective: To evaluate a biochemical score for diagnosing non-alcoholic steatohepatitis. Methods: An observational, cross sectional study was carried out for a period of two years in the Department of Hepatology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. 43 patients of Non-alcoholic fatty liver disease (NAFLD) attending at department of Hepatology were selected and underwent for biochemical investigations and liver biopsy with NAFLD Activity Score (NAS). Results: A biochemical score (TAAG score) assigned 1 point for each parameter (fasting serum triglyceride >ULN, alanine aminotransferase >ULN, AST/ALT ratio (AAR) ≤1 and gamma-glutamyl transferase >ULN) was evaluated. TAAG score ≥3 was present in 32.5% of study population and 40% of NASH patients. It had a sensitivity of 40%, specificity 26% and AUROC 0.54. Conclusion: Biochemical scoring system comprising traditional biomarkers did not significantly predict NASH. Biopsy is the only way to estimate steatohepatitis and/or fibrosis. Bangladesh J Medicine July 2019; 30(2) : 58-62